(untitled) (Global Journal of Medical Research, 2024)
Pharmaceutical chemistry seeks to discover and develop new chemical molecules that can be useful as medicines in addition to the possibility of improvement in some molecular physicochemical aspect These modifications cannot alter the pharmacophoric group which is the chemical functional group responsible for the therapeutic effects KOROLKOVAS 1982 Thus our objective was to present the physicochemical aspects related to the association of vitamin K with warfarin molecule VAR in order to develop the Varfa-K Prototype a new drug that has fewer toxic effects mainly reducing bleeding events caused by VAR Therefore we used the methodology of molecular association and insertion of bulky groups By adding a molecule vitamin K to the parent drug and its own antidote against bleeding